Effect of Different Intensities of Harsh Reliance of Auditory Stimulation on Static Balance in 5-12 Years Old Children With Cerebral Palsy in Tehran City, Iran - Masomeh Esmailpour Nosar; Seyed Ali Hosseini; Nazila Akbarfahimi; Seyed Farhad Tabatabai Ghomshe (University of Social Welfare and Rehabilitation Sciences, 2018)
Objective control dysfunction is a serious problem in children with Cerebral Palsy (CP). This study aimed to investigate the impact of different intensities, harsh reliance of auditory stimulation on static balance in 5-12 years old children with bilateral spastic cerebral palsy. Materials & Methods This analytical descriptive study, twenty 5-12 years old children (8 boys and 12 girls, Mean±SD age: 7.10±2.03 y) with cerebral palsy participated. They were selected by the convenience sampling method. Children with CP were included in the study if they had bilateral spastic CP (diagnosed by neurologist), aged 5 to 12 years, had level I and II CP according to Gross Motor Function Classification System (GMFCS), could stand independently without any support for at least 30 seconds, had no history of surgical treatment or received injection of botulinum toxin within six months prior to the study and not a candidate for such, got scores between 1 to 3 according to Modified Ashworth Scales (MAS) in plantar flexors, and understood verbal comments. They were excluded from the study if they had vision or hearing impairments and uncontrolled epilepsy. Modified Ashworth Scales, Force Plate (during eyes open) and SPARCLE questionnaire were employed to assess muscle tone, static balance, and cognition level, respectively. The central of mass signals were collected at a sampling frequency of 100 Hz, over a period of 30 seconds using a single piezoelectric force platform (Model 9286; Kisler, Switzerland, Bioware 4-0-12). All participants were tested in standing position with eyes opened. The participants stood independently, with bare feet, on the markers in the center of the platform with arms at the sides, while looking straight ahead at the spot in front of them. The participants listened to impure auditory stimulation with harsh and low high intensity on a hard surface and soft force plate for three times. The four tasks were 1. Standing on soft surface while listening to impure auditory stimulation with harsh high intensity; 2. Standing on soft surface while listening to impure auditory stimulation with harsh low intensity; 3. Standing on hard surface while listening to impure auditory stimulation with harsh low intensity; and 4. Standing on hard surface while listening to impure auditory stimulation with harsh high intensity. Between the tasks, a break was provided during which they could rest on the chair for at least 5 minutes. Then the process repeated with auditory stimulation harsh low intensity. The average results across the three times were calculated for each participant. The data were filtered and anterior-posterior, phase plane portrait rate and velocity were measured with MATLAB (R2010a). Data normality distribution was tested using Shapiro-Wilk test which revealed the normality in distribution of the data (P<0.05). The independent t test was used to compare the results of anterior-posterior, phase plane portrait rate and velocity for each condition (harsh high intensity on a hard surface, soft force plate, harsh low intensity on a hard and soft surface of force plate). All statistical analyses were performed in SPSS V. 16. The significance level was set at P<0.05 for all tests. Results The effect of harsh high intensity auditory stimulation on the hard and soft surface of the plate anterior -posterior rate (P<0.001) and velocity (P<0.001) were significant. There was no significant effect of harsh low intensity auditory stimulation on the hard and soft surface of the plate anterior-posterior rate (P=0.38) and velocity (P=0.722). Conclusion According to this study, the harsh high intensity auditory stimulation on hard and soft surfaces with eyes opened affect the speed rate, anterior-posterior, phase plane portrait page, and static balance in children with bilateral spastic CP. Regarding this result, balance programming may improve the static balance in these children.